Humaniora i välfärdssamhället Kunskapshistorier om efterkrigstiden - Östling, Johan; Jansson, Anton; Svensson Stringberg, Ragni (Kriterium, 2023)
This book highlights the diverse roles of the humanities in the history of the Swedish welfare society. This society has often been seen as dominated by an instrumental view of knowledge that rewarded the social sciences, natural sciences and technology, but the contributions in this book show the significant role that the humanities played in the Swedish welfare state. Various forms of humanistic knowledge and knowledge actors were part of large networks and left a clear mark on the public sphere and society at large. A narrative of the marginalization and crisis of the humanities in the postwar period must therefore be problematized. This edited volume brings together some twenty scholars from a number of humanities disciplines (history, history of ideas, media history, literary studies, archaeology, education, etc.). Much of the current research on the history of the humanities conducted in Sweden today is brought together here and put in relation to international discussions in fields such as history of humanities, history of knowledge, etc. The book is a sibling to the monograph Humanister i offentligheten, which was published in 2022.